2013
DOI: 10.1038/srep02935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new high-throughput method for identifying quorum quenching bacteria

Abstract: Quorum sensing (QS) is a population-dependent mechanism for bacteria to synchronize social behaviors such as secretion of virulence factors. The enzymatic interruption of QS, termed quorum quenching (QQ), has been suggested as a promising alternative anti-virulence approach. In order to efficiently identify QQ bacteria, we developed a simple, sensitive and high-throughput method based on the biosensor Agrobacterium tumefaciens A136. This method effectively eliminates false positives caused by inhibition of gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…In a previous study, we demonstrated that the flounder mucusderived strain Muricauda olearia Th120 has strong AHL degradative activity (14) and could decrease biofilm formation and virulence in P. aeruginosa PAO1 (19). In the present study, we identified the momL gene that encodes a novel secretory AHL lactonase from Th120.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…In a previous study, we demonstrated that the flounder mucusderived strain Muricauda olearia Th120 has strong AHL degradative activity (14) and could decrease biofilm formation and virulence in P. aeruginosa PAO1 (19). In the present study, we identified the momL gene that encodes a novel secretory AHL lactonase from Th120.…”
mentioning
confidence: 67%
“…The cell suspension was sonicated on ice, and the supernatant and cell content were collected after centrifugation and filtration. The C 6 -and C 12 -HSL degradative activities of these sample were measured using the A136 liquid X-Gal assay, which applies 1,4-piperazinediethanesulfonic acid (PIPES) buffer (pH 6.7) to prevent alkaline hydrolysis (14). In addition, the acidification test was used to demonstrate whether the AHL degradation was due to lactonase activity (6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These strains often lack the ability to produce native QS signals; however, they are able to respond to exogenous autoinducers, often with a clearly detectable phenotype, such as violacein pigment production in Chromobacterium violaceum CV026 (85,86) and bioluminescence production in V. harveyi (87) or Agrobacterium tumefaciens A136 (88). Using such reporter strains, numerous compounds degrading or modifying AHL have been identified, including signal molecules and AHL analogues (reviewed in references 16 and 19).…”
Section: Figmentioning
confidence: 99%